Application of Play Methods in Developing Early Math Skills during Learning from Home - Setiawati, Tia; Yanuarsari, Revita; Maulani, Susan (Indonesian Journal of Adult and Community Education, 2023)
Early mathematical ability is a basic ability possessed by children, the main problem in this study is the decline in early mathematical abilities of children aged 5-6 years in learning carried out from home with the play method at Umi Bina Mandiri PAUD caused by learning activities carried out from home. home so that children are less stimulated in early mathematical abilities. The purpose of this study was to obtain a description of information and data about children's activities, the role of teachers, and children's learning outcomes in early mathematics through the play from home method for children aged 5-6 years. This research uses a qualitative approach with a case study method. The data sources are the principal, 2 teachers and group B students. The results of the study (1) Children's activities in learning from home through the play method in developing early mathematical abilities seen from the implementation and responses show the success of teachers and parents in facilitating and assisting children in each lesson (2) The teacher's role in learning from home in planning, implementation, evaluation, support systems, and learning design, this can be seen from the teacher being able to make learning from home interesting and creative through the active play method. (3) The results of children's learning in developing early mathematical abilities through the play method during learning from home are seen from the results of observations of children who have developed as expected.